PITCH VALUES IN CHINESE SOCIAL AND COMMERCIAL ADVERTISEMENT DISCOURSE - KARAVAEVA, V.G; ZHANG, J; ANDROSOVA, S.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
The paper raises an issue of the lexical tone and pitch interaction in Chinese radio advertisement discourse. Vast expansion of advertisement and its high manipulative potential put it in the center of researchers' attention. The importance of fundamental frequency variation study in connected speech is determined by the needs of automatic speech production and perception. Attracting listener's attention and keeping information in their memory for a considerable time period, advertising becomes one of the sources of standard speech behavior patterns and determines prosodic arrangement of the utterance including pitch level. The paper presents new data on the level values of the 4 lexical tones in Chines manifested in advertisement taking into account gender and position in a word. The acoustic cues of 3 relevant prosodic features were analyzed: pitch level, pitch range, initial pitch level and terminal pitch level. The material for the research was comprised of 59 commercials and 72 social radio ads. Besides the well-known gender variance, high dependency of range values on the utterance style and position in the word was found. Considering the issue from the angle of the utterance informative structure might be the focus of further studies.